A framework of games design for internet and e-commerce subject towards an effective learning - Bahari, Rohaizah (2017)
This study attempts to develop a framework for the use of gamification in education. Therefore, this paper focuses on students in semester 4 taken Diploma in Business Studies for Internet and E-commerce subject. The main objective of this study was to 1) design framework game for learning activities, 2) to develop a form of learning games of the framework is generated, 3) to evaluate the effectiveness of games for learning activities for the subject of Internet and E-Commerce (ITE 2513) this. MARA Professional College (KPM) interaction between lecturers and students is limited, sometimes it is boring and it can be very challenging for teaching methodology. However, this problem can be solved with a short learning and practice phase. For this reason, we analyze the potential of using gamification approaches to increase learning management for this subject. Based on the analysis of student performance, we have created a framework for the use of gamification in the subject of Internet and e-commerce through Learning Management System (LMS). Through this system it will be able to help improve student performance. This framework allows users to explore the user interface in Learning Management System. By reflecting on the results of the first study with this framework, we present a set of guidelines for designing and evaluating the use of the domain gamified LMS, which can serve as support for the development of the future.